Ngowan Sapeh's Practice of Cooperation in The Perspective of Islamic Law - Pujiati, Tri; istiqomah, iis (Et-Tijarie, 2023)
This study aims to find out how the concept of cooperation in the Sumenep area, Madura and the practice of cooperation are analyzed with Islamic law.This study uses qualitative research, and this type of research uses analysis with a sociological normative approach. Where the approach used in this study is to use secondary data and primary data from books, interviews and other materials. This normative approach is about the implementation of normative legal provisions in its actions to every specific event that occurs in a society. The approach used in this writing is the sociological normative method where this normative approach examines the practice of ngowan sapeh cooperation in the perspective of Islamic law. This data analysis technique also uses data collection methods, namely by conducting observations, interviews and also recommendations in the practice of ngowan sapeh cooperation in the perspective of Islamic law. The results of this study found that the practice of ngowan sapeh cooperation in the perspective of Islamic law is a form of cooperation that occurs in the community in Aeng Tong-tong Village, in general, the Aeng Tong-tong community is more cooperative in raising cows (ngowan sapeh) because raising cows has become a common phenomenon in the community in satisfying their own lives and their families.